Induction of apoptosis in cervical cancer cells by the duplex drug 5-FdU-ECyd, coupling 2'-deoxy-5-fluorouridine and 3'-C-ethinylcytidine - Schott, Sarah; Brüning, Ansgar (Gynecologic oncology, 2014)
OBJECTIVE: Therapeutic options are limited for patients with advanced cervical cancer, and more effective drugs with favorable side-effect profiles are needed. We developed a nucleoside analogue duplex drug (5-FdU-ECyd), in which the DNA synthesis inhibitor 5-fluorodeoxyuridine is coupled to the RNA synthesis inhibitor 3'-C-ethinylcytidine. We therefore aimed to test its efficacy in cervical carcinoma cells in vitro and to establish its mechanism of action. - METHODS: The cytotoxic effects of 5-FdU-ECyd on cervical cancer cells were assessed using the MTT assay, clonality assays, FACScan analysis, and its effect on cancer cell spheroids. Mechanisms of cell death were analyzed by Western blotting for apoptosis and autophagy pathways and mitochondrial membrane potential. - RESULTS: HeLa, CaSki, SiHa, and Me180 cervical cancer cells were highly sensitive to 5-FdU-ECyd in both 2- and 3-dimensional cancer models. The cell death induced by 5-FdU-ECyd was associated with characteristic morphological and biochemical signs of apoptosis, including nuclear chromatin condensation and fragmentation, PARP cleavage, and a breakdown in mitochondrial membrane potential. 5-FdU-ECyd treatment led to an early S-phase arrest and drastically reduced expression of the anti-apoptosis protein Mcl-1 and increased signaling via the JNK and p38 MAPK pathways. - CONCLUSIONS: 5-FdU-ECyd is highly cytotoxic in cervical cancer cells and exploits apoptosis pathways that might be specific to cancer, but not normal cells. 5-FdU-ECyd might represent a new chemotherapeutic option for patients with advanced or treatment refractory cervical cancer.
Gesehen am 04.12.2020